PERAN MANAJERIAL SUMBER DAYA MANUSIA SEBAGAI KEUNGGULAN BERSAING DALAM MENINGKATKAN KINERJA ORGANISASI YANG BERKELANJUTAN - Uli Wildan Nuryanto (Institut Agama Islam Negeri Padangsidimpuan, 2020)
AbstractThe chemical manufacturing sector is one of the supporters of the domestic economy which contributes to the value of domestic exports of 6.41% of total exports. However, in the last 3 years there was a significant decrease in production volume which caused the growth of the chemical industry sector to only reach 3.48%, this value is still below the national economic growth. This shows the importance of competitive advantage in facing global competition. Therefore, this study was conducted to examine the indicators that influence competitive advantage viewed from the perspective of human resources by using managerial functions on sustainable organizational performance by using environmental, social and economic dimensions. The study was conducted in the chemical manufacturing industry sector in Banten Province of 110 respondents with criteria as managerial level or decision making with a minimum working period of 2 years and using a purposive sampling method. The analytical method uses Smart PLS 3 against 4 indicators of competitive advantage and 28 indicators of organizational performance that is sustainable. The results of the outer model show that all indicators of competitive advantage can build latent variables, while of 28 indicators of sustainable organizational performance there are 3 indicators that have loading factors below 0.70, so that only 25 indicators are able to build latent variables. The inner model results show that the model built has good goodness of fit, while the results of the hypothesis test show a significant influence between the variables of competitive advantage on sustainable organizational performance with a magnitude of influence of 50.3%.Keywords: Managerial function, Competitive Advantage, Sustainable Organizational Performance.